Kekerasan Subkultur Underground dalam Novel Hebi Ni Piasu Karya Hitomi Kanehara Perspektif Hegemoni Maskulinitas Connell - Muhammad, Aditya Martin (East Asian Review, 2025)
This article will focus on the discovery of violence within the underground subculture in Japan. Masculinity in Japan's mass culture is deeply intertwined with its hegemonic nature, and this is no exception within subcultural currents. Hegemony can form from various aspects, ranging from ideology to sex. Subcultures, which fundamentally strive to separate themselves from mass culture, remain influenced by this hegemony. Environmental factors and the collective memory of each individual also play an unavoidable role in this regard. Hebi Ni Piasu, a novel by Hitomi Kanehara, was selected because it depicts how individuals within the subculture interact in spaces of violence. This article will address two main questions: 1) how the characters interact and respond within violent spaces in the subculture and 2) how the culture of violence in the subculture shapes gender identity in the novel. Using Connell's perspective of hegemonic masculinity and a qualitative descriptive method, the findings reveal that: 1) The violence—whether conscious or unconscious—performed by the characters shapes interactions based on power relations, unconsciously constructing perceptions of subject and object. 2) Hegemonic masculinity clearly dictates how the culture of violence operates within the subculture by exerting power over the characters. The power dynamics in determining which genders and identities become dominant or subordinate within the subculture trap the novel's characters in hegemonic masculinity.